Effect of Resin Acid and Zinc Oxide on Immune Status of Weaned Piglets Challenged With E. coli Lipopolysaccharide - Guan, Xiaonan; Santos, Regiane R.; Kettunen, Hannele; Vuorenmaa, Juhani; Molist, Francesc (Frontiers in Veterinary Science, 2021)
With the ban of zinc oxide (ZnO) at high dosages in piglet diets in Europe by 2022, alternative nutritional solutions are being tested to support piglet immune defence during their weaning, the most critical and stressful moment of pig production. The present study evaluated the effect of zinc oxide (ZnO; 2500 mg/kg diet) and resin acid concentrate (RAC; 200 mg/kg diet) on the immune defence of weaned piglets challenged with lipopolysaccharide (LPS). Piglets were challenged at days 7 and 21 post-weaning, and blood was sampled 1.5 and 3.0 h after each challenge to determine serum levels of pro- and anti-inflammatory cytokines. The levels of serum tumour necrosis factor-alpha (TNF-α) and interleukin 8 (IL-8) increased at days 7 and 21, and those of IL-6 at day 21 when challenged piglets were fed a diet supplemented with ZnO. In challenged piglets fed with RAC, the serum levels of IL-1β, IL-6, IL-8, IL-10 and TNF-α were increased at days 7 and 21, except for that of IL-1β, which was not affected at day 21. The increased levels of these cytokines indicate the successful immune-modulatory effect of ZnO and RAC, which appears as a candidate to replace ZnO in weaned piglets’ diets.